2023
DOI: 10.1097/cce.0000000000000861
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation for COVID-19: Comparison of Outcomes to Non-COVID-19–Related Viral Acute Respiratory Distress Syndrome From the Extracorporeal Life Support Organization Registry

Abstract: OBJECTIVES: To compare complications and mortality between patients that required extracorporeal membrane oxygenation (ECMO) support for acute respiratory distress syndrome (ARDS) due to COVID-19 and non-COVID-19 viral pathogens. DESIGN: Retrospective observational cohort study. SETTING: Adult patients in the Extracorporeal Life Support Organization registry. PATIENTS: Nine-thousand two-hundred ninety-one patients that required ECMO for viral mediated ARDS between January 2017 and December 2021. INTERV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(43 reference statements)
0
3
1
Order By: Relevance
“…This finding differs from previous smaller studies examining the outcomes of V-V ECMO for COVID-related respiratory failure, which have shown comparable rates of mortality to historical V-V ECMO 9,10 . However, our findings are similar to those of Chandel et al 12 who reported a 50.2% mortality for V-V ECMO for COVID-19 (n=8136) versus 34.5% among V-V ECMO for non-COVID causes (n=1155). Barbaro et al 13 demonstrated that early in the pandemic, patients were kept on mechanical ventilation for longer periods of time before being placed on ECMO and that late-adopting centers had significantly higher mortality rates, both factors that may have contributed to the high mortality rates seen in this study for patients undergoing V-V ECMO for COVID causes.…”
Section: Discussioncontrasting
confidence: 97%
“…This finding differs from previous smaller studies examining the outcomes of V-V ECMO for COVID-related respiratory failure, which have shown comparable rates of mortality to historical V-V ECMO 9,10 . However, our findings are similar to those of Chandel et al 12 who reported a 50.2% mortality for V-V ECMO for COVID-19 (n=8136) versus 34.5% among V-V ECMO for non-COVID causes (n=1155). Barbaro et al 13 demonstrated that early in the pandemic, patients were kept on mechanical ventilation for longer periods of time before being placed on ECMO and that late-adopting centers had significantly higher mortality rates, both factors that may have contributed to the high mortality rates seen in this study for patients undergoing V-V ECMO for COVID causes.…”
Section: Discussioncontrasting
confidence: 97%
“…Some studies compared ECMO in non-COVID-ARDS patients and COVID-ARDS patients. Although similar results were gathered about oxygenation (99,100), the treatment time and complications were different. Chandel et al (99) analyzed 9,271 patients who required ECMO between 2017 and 2021.…”
Section: Ecmo In Non Covid-ards Versus Covid-ards Patientsmentioning
confidence: 61%
“…The COVID-19 pandemic resulted in increased referrals for VV ECMO ( 1 ). A prior analysis of the ELSO registry suggested that patients with ARDS related to COVID-19 had worse VV ECMO-related outcomes compared with patients with ARDS related to other conditions ( 14 ). However, it is not clear if these observed differences in outcome remain when considering only patients supported with prolonged VV ECMO.…”
Section: Discussionmentioning
confidence: 99%